INVESTIGATING THE USE OF CONTEXTUAL TEACHING AND LEARNING ON STUDENTS’ WRITING RECOUNT TEXT: A CASE ON TEACHING METHOD - Vitalia Hanako Murni Simanjuntak; Indah Sari; Daniel Frengki Kamengko; Isry Laila Syathroh; Erti Manurung; Herman Herman; Nguyen Van Thao (University of Kuningan, 2025)
This research was designed to find the effect of Contextual Teaching and Learning on student’s writing recount text at grade ten of SMA Negeri 6 Pematangsiantar. To answer the problems the researchers used theories such as Berns & Erickson (2001), Harmer (2004), Knapp and Watkins (2005). The study employed a quantitative research design. As an experimental investigation, its goal was to determine whether the implemented method had any impact on the subject. In this research, in collecting the data the researchers had to do three steps: pre-test, treatment, post-test. The researchers discovered that CTL has a significant impact on students' ability to write recount texts. This is evident from the post-test scores of the experimental class, where the writer applied the CTL treatment. After calculating the data, the researchers found the mean of experimental class was 76,76 and the mean of control class was 61,83. The calculation of t-test, the total t- obtained value of the research is 4.63 with the degree of freedom (df) was (30+30)-2=58 and level of significant 2.5% (0.025), so the value table of t-table was 2.00. It shows that t- obtained value is higher than t-table (4.63> 2.00). Therefore, the Alternative Hypothesis (Ha) was accepted and the Null Hypothesis (Ho) was rejected. It means that Contextual Teaching and Learning was more significant than Grammar Translation Method in writing recount text at grade ten of SMA Negeri 6 Pematangsiantar.